Zinc oxide and copper oxide synthesized by thermal treatment method - Lee, Phin Jit (2014)
In this work, zinc oxide and copper oxide nanoparticles have been synthesized via thermal treatment method. In a typical work, salt nitrate as precursor and polyvinyl pyrrolidone as capping agent were dissolved and stirred in deionized water (as solvent) using magnetic stirrer accompanied with heating. Then, the hot mixture dried in oven for 24 hr was ground with mortar for at least 20 min to form fine powder. Lastly, the fine powder was underwent heat treatment at temperature ranged from 400 to 900 oC. The oxides nanoparticles formed were characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD), Fourrier Transform infrared (FT-IR) spectroscopy, transmission electron microscopy (TEM), and ultraviolet-visible (UV-Vis) spectroscopy. From TGA, it was found that the capping agent, polyvinyl pyrrolidone can be removed by calcination at temperature 450 and 500 oC to form pure copper oxide and zinc oxide respectively. This result was testified by FT-IR such that no characteristic absorption bands of polyvinyl pyrrolidone was detected in copper oxide and zinc oxide calcined at temperature 450 and 500 oC respectively, except corresponded oxide bands. In XRD analysis, broad diffraction peaks of zinc oxide and copper oxide nanoparticles were observed at temperature of 400 oC, showed that hexagonal wurzite structure and monoclinic structure crystals corresponded to zinc oxide and copper oxide have formed at this temperature. By increasing the heating temperature from 400 to 900 oC, the crystallites size of zinc oxide and copper oxide nanoparticles increased from ~18.9 to 96.4 nm and from ~19.5 to 36.2 nm, respectively. Meanwhile, TEM also showed that particle size of zinc oxide and copper oxide increased with increasing heating temperature. It was found that zinc oxide nanoparticles demonstrated spherical shape while copper oxide showed rod shape at temperature below 700 oC and then spherical shape as heating temperature increased. From UV-Vis measurement, estimated direct energy band gap of zinc oxide and copper oxide decreased with increased heating temperature while indirect energy band gap of copper oxide showed increasing trend.